2013
DOI: 10.2106/jbjs.l.01386
|View full text |Cite
|
Sign up to set email alerts
|

Growing-Rod Graduates: Lessons Learned from Ninety-nine Patients Who Completed Lengthening

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(76 citation statements)
references
References 8 publications
1
72
0
3
Order By: Relevance
“…29,30,[38][39][40][41][42][43] Implant complications such as anchor malfunction (pullout from the spine, erosion through the rib) and rod breakage are common (Fig 9). Distraction-based posterior implants often produce kyphosis, which may result in an unfavorable overall sagittal plane balance.…”
Section: Complications Of Distraction-based Implantsmentioning
confidence: 99%
“…29,30,[38][39][40][41][42][43] Implant complications such as anchor malfunction (pullout from the spine, erosion through the rib) and rod breakage are common (Fig 9). Distraction-based posterior implants often produce kyphosis, which may result in an unfavorable overall sagittal plane balance.…”
Section: Complications Of Distraction-based Implantsmentioning
confidence: 99%
“…Until recently, the literature was sparse, but Flynn et al reported a series of 99 patients, aged 11-13 years, undergoing lengthening over a mean of 5 years [31].…”
Section: Definitive Fusion Surgerymentioning
confidence: 99%
“…Proximally hooks supplemented with or without wires can be used to prevent complications of proximal screw pull out or migration. 30 Complications of growing-rod techniques are largely related to the need for multiple procedures. 27 Lengthening procedures usually are performed every 6-9 mo until the child reaches appropriate size or age for spinal fusion.…”
Section: Operative Managementmentioning
confidence: 99%